2003
DOI: 10.1038/sj.bmt.1703840
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose or intermediate-dose cyclophosphamide plus granulocyte colony-stimulating factor for progenitor cell mobilisation in patients with multiple myeloma

Abstract: Summary:Cyclophosphamide (CY) combined with granulocyte colony-stimulating factor (G-CSF) is commonly used to mobilise blood progenitor cells to support high-dose therapy in patients with multiple myeloma (MM). The optimal dose of CY in this setting is unknown. We have retrospectively analysed mobilisation efficiency and need for supportive care in 57 patients with newly diagnosed myeloma previously treated with VAD7local radiotherapy. The patients were mobilised either with low-dose CY (LD-CY, 1.2-2 g/m 2 ) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 17 publications
(27 reference statements)
4
64
1
1
Order By: Relevance
“…Desikan et al 29 reported increased hospitalization and transfusions in patients who underwent mobilization with G-CSF plus high-dose CY than with G-CSF alone. In addition, Jantunen et al 41 and Fitoussi et al 40 reported more hospital days, more days of i.v. antibiotics and more blood transfusions in patients who underwent mobilization with higher doses of chemotherapy than in those who received lower doses.…”
Section: G-csf In Conjunction With Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…Desikan et al 29 reported increased hospitalization and transfusions in patients who underwent mobilization with G-CSF plus high-dose CY than with G-CSF alone. In addition, Jantunen et al 41 and Fitoussi et al 40 reported more hospital days, more days of i.v. antibiotics and more blood transfusions in patients who underwent mobilization with higher doses of chemotherapy than in those who received lower doses.…”
Section: G-csf In Conjunction With Chemotherapymentioning
confidence: 99%
“…Compared with mobilization regimens using G-CSF alone, chemomobilization is associated with increased morbidity, greater risk of infection, more hospital admissions, transfusions, antibiotic therapy and considerably greater cost overall. 29,[39][40][41][42] Although treatment-related mortality is rare, significant morbidity related to neutropenia that can often require hospitalization has been described, and many reports point to greater resource utilization with chemomobilization than with cytokine-alone mobilization. 29,37,39 Koc et al 39 found that although treatment with CY plus G-CSF resulted in greater stem cell yield than did treatment with GM-CSF plus G-CSF, it also caused greater morbidity.…”
Section: G-csf In Conjunction With Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…15 CY has also been included in mobilization regimens with the aim to reduce graft contamination by clonal plasma cells (PCs); however, there are no data suggesting the usefulness of this drug, both in upgrading the quality of response before ASCT and in reducing PCs contamination of the harvest. Moreover, although circulating clonal PCs at diagnosis have been associated with early relapse after ASCT, 16 ex vivo purging had no impact on ASCT outcome in MM patients.…”
mentioning
confidence: 99%
“…20 Chemomobilization is also associated with dose-dependent patient morbidity, greater risk of infection and febrile neutropenia, more hospital admissions and drug-specific toxicities, compared with G-CSF alone. 21 In addition, chemotherapy may damage the bone marrow microenvironment and impair engraftment with possible long-term adverse effects and compromised future mobilization attempts. 3,13 Thus, unless the antitumor activity is proven, chemotherapy to mobilize HSCs may not be cost-effective and may result in some risks for patients.…”
mentioning
confidence: 99%